Improvement of the Acoustic Attenuation of Plaster Composites by the Addition of Short-Fibre Reinforcement - P. Kulhavý; A. Samková; M. Petru; M. Pechociakova (Advances in Materials Science and Engineering)
Noise attenuation is a key contemporary issue associated with the protection of human health. In this study, the possibilities of affecting acoustic properties of plaster composites by the addition of short-fibre reinforcement are described. The improvement of attenuation abilities was first verified using a simple numerical model with a pure plaster followed by using a reinforced plaster. The model results revealed a mutual correlation between the fibre ratio and dissipated acoustic energy. Hence, typical plasters used in the building industry (e.g., plaster, lime cement, and cement) are used as the base materials of the tested composites. The reinforcing dispersion in the form of short fibres (basalt and glass) with a defined length was selected after evidence from previously reported studies and after the comparison of some other fibres with respect to the trade-off between the rendered mechanical properties and cost. Transfer functions of the tested samples were measured using an impedance tube with two microphones, followed by the calculation of the total acoustic absorption. On the other hand, cement and plaster materials exhibited a low damping ability, and the absorption could be considerably increased by the addition of fibres, especially in the area around 1 kHz. In contrast, the UM plaster exhibited good damping properties even without the dispersion, and the addition of improper fibres such as glass ones possibly worsened the properties. The acoustic attenuation of the plaster composites can be improved by the appropriate combination of the base material and fibre dispersion. However, it is not possible to generalise this improvement for all possible combinations.